Vitamin D deficiency in childhood obesity is associated with high levels of circulating inflammatory mediators, and low insulin sensitivity - Reyman, M; Verrijn Stuart, A A; van Summeren, M; Rakhshandehroo, M; Nuboer, R; de Boer, F K; van den Ham, H J; Kalkhoven, E; Prakken, B; Schipper, H S (International Journal of Obesity, 2014)
Hypothesis: Childhood obesity is accompanied by low-grade systemic inflammation, which contributes to the development of insulin resistance and cardiovascular complications later in life. As vitamin D exhibits profound immunomodulatory functions and vitamin D deficiency is highly prevalent in childhood obesity, we hypothesized that vitamin D deficiency in childhood obesity coincides with enhanced systemic inflammation and reduced insulin sensitivity. Methods: In a cross-sectional study of 64 obese and 32 healthy children aged 6–16 years, comprehensive profiling of 32 circulating inflammatory mediators was performed, together with assessment of 25-hydroxyvitamin D (25(OH)D) levels and measures for insulin sensitivity. Results: Severe vitamin D insufficiency, which is further referred to as vitamin D deficiency, was defined as a 25(OH)D level ⩽37.5 nmol l –1 , and was highly prevalent in obese (56%) versus healthy control children (16%). Throughout the study, 25(OH)D-deficient children were compared with the other children, including 25(OH)D insufficient (37.5–50 nmol l –1 ) and 25(OH)D sufficient children (⩾50 nmol l –1 ). First, 25(OH)D-deficient obese children showed a lower insulin sensitivity than other obese children, as measured by a lower quantitative insulin sensitivity check index. Second, the association between 25(OH)D deficiency and insulin resistance in childhood obesity was confirmed with multiple regression analysis. Third, 25(OH)D-deficient obese children showed higher levels of the inflammatory mediators cathepsin S, chemerin and soluble vascular adhesion molecule (sVCAM), compared with the other obese children. Finally, hierarchical cluster analysis revealed an over-representation of 25(OH)D deficiency in obese children expressing inflammatory mediator clusters with high levels of cathepsin S, sVCAM and chemerin. Conclusion: 25(OH)D deficiency in childhood obesity was associated with enhanced systemic inflammation and reduced insulin sensitivity. The high cathepsin S and sVCAM levels may reflect activation of a pro-inflammatory, pro-diabetic and atherogenic pathway, which could be inhibited by vitamin D supplementation.